2012
DOI: 10.26719/2012.18.12.1257
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of haemoglobinopathies: a single-centre, cross-sectional study from Islamabad, Pakistan

Abstract: Thalassaemia is the most frequent hereditary disorder in Pakistan, with an estimated 8-10 million carriers. This single-centre study reported the frequency of haemoglobinopathies among 504 consecutive cases visiting Islamabad Diagnostic Centre for haemoglobin electrophoresis from July 2010 to February 2011. Haemoglobin electrophoresis was performed on cellulose acetate membrane, followed by staining and densitometric scanning of bands. A total of 143 (28.4%) subjects had haemoglobinopathies. The most predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…These hereditary disorders of Hb pose a massive health problem in many third world countries including India, Pakistan, and Iran [7]. The overall frequency of hemoglobinopathies was 34.2%, among which beta Thalassemia minor was 51.8% and Hb D trait was 6.7% and Beta Thalassemia major was 24.1%.7 Nearly similar findings were observed in other studies conducted by in Pakistan [8,9]. Thalassemias are inheritable common genetic disorder worldwide due to alteration in haemoglobin (Hb) production.…”
Section: Discussionsupporting
confidence: 66%
“…These hereditary disorders of Hb pose a massive health problem in many third world countries including India, Pakistan, and Iran [7]. The overall frequency of hemoglobinopathies was 34.2%, among which beta Thalassemia minor was 51.8% and Hb D trait was 6.7% and Beta Thalassemia major was 24.1%.7 Nearly similar findings were observed in other studies conducted by in Pakistan [8,9]. Thalassemias are inheritable common genetic disorder worldwide due to alteration in haemoglobin (Hb) production.…”
Section: Discussionsupporting
confidence: 66%
“…In Karachi a very high frequency also noted 75.9% for Β-Thalassemia by Shabbir et al, 2016 13 . While in Islamabad 27% cases also detected for Β-Thalassemia by Waheed et al, 2012 11 .…”
Section: Discussionmentioning
confidence: 93%
“…The higher frequency by us is contrasts with some others. A study conducted in Islamabad revealed (28.4 %) by Waheed et al 11 , while Saleem et al 12 from Northern Areas of KP (25 %) and about 34.2% from Karachi 13 . This may be attributed due to the patient distribution, because we analysed the samples size from single centre and did not represented the whole population.…”
Section: Discussionmentioning
confidence: 95%
“… 9 In contrast to our results, Waheed et al reported the overall frequency of hemoglobinopathies 28.4% which is exactly twice of the frequency observed in our study. 10 Another report from Khyber Pakhtunkhwa (KPK) showed 48.9% of the study subjects suffering from various hemoglobinopathies. 11 The underlying reason for the relatively low frequency observed herein might be the misdiagnosis of β-TT as iron deficiency anemia (IDA).…”
Section: Discussionmentioning
confidence: 98%